INVESTIGATION OF HARDINESS PERSONALITY ON POST-DEFEAT STRESS LEVELS IN FOOTBALL ATHLETES - Kurniawan, Ari; Widiantoro, Wahyu; Rahma, Izzah Annisatur (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2024)
AbstractThis study aims to analyze the relationship between hardiness personality and post-defeat stress levels in adolescent soccer players. Hardiness is a psychological resilience trait consisting of three main components: commitment, control, and challenge, which helps individuals manage life's pressures and challenges. This study used a quantitative method with a survey technique, involving 70 adolescent soccer players as respondents. Data were collected through a hardiness questionnaire and a post-defeat stress questionnaire. Data analysis was carried out using the Pearson correlation test to determine the relationship between these variables. The results showed a significant negative correlation between hardiness and post-defeat stress levels (r = -0.254, p < 0.05). Based on the results of the Pearson correlation test, there was a significant negative relationship between hardiness personality and stress with a correlation value of -0.254 and a significance of 0.034 (p < 0.05). This shows that the higher a person's hardiness level, the lower the level of stress they experience. However, the degree of this relationship is relatively weak because of the low correlation value. This means that hardiness personality only has a small effect on the stress levels of the respondents. These results have practical implications in the development of mental training programs to improve hardiness in athletes. Further research is recommended to explore the effects of hardiness enhancement interventions and examine additional variables, such as coping strategies and social support, that may strengthen psychological resilience in a sport context.AbstrakPenelitian ini bertujuan untuk menganalisis hubungan antara kepribadian hardiness dan tingkat stres pasca kekalahan pada pemain sepak bola remaja. Hardiness adalah sifat ketahanan psikologis yang terdiri dari tiga komponen utama: komitmen, kontrol, dan tantangan, yang membantu individu dalam mengelola tekanan dan tantangan hidup. Penelitian ini menggunakan metode kuantitatif dengan teknik survei, melibatkan 70 pemain sepak bola remaja sebagai responden. Data dikumpulkan melalui kuesioner hardiness dan kuesioner stress pasca kekalahan. Analisis data dilakukan dengan uji korelasi Pearson untuk menentukan hubungan antara variabel-variabel tersebut. Hasil penelitian menunjukkan korelasi negatif yang signifikan antara hardiness dan tingkat stres pasca kekalahan (r = -0.254, p < 0,05). Berdasarkan hasil uji korelasi Pearson, terdapat hubungan negatif yang signifikan antara kepribadian hardiness dan stres dengan nilai korelasi sebesar -0,254 dan signifikansi 0,034 (p < 0,05). Hal ini menunjukkan bahwa semakin tinggi tingkat hardiness seseorang, semakin rendah tingkat stres yang dialaminya. Namun, derajat hubungan ini tergolong lemah karena nilai korelasi yang rendah. Artinya, kepribadian hardiness hanya memiliki pengaruh kecil terhadap tingkat stres para responden. Hasil ini memiliki implikasi praktis dalam pengembangan program pelatihan mental untuk meningkatkan hardiness pada atlet. Penelitian selanjutnya disarankan untuk mengeksplorasi pengaruh intervensi peningkatan hardiness dan mengkaji variabel tambahan, seperti strategi koping dan dukungan sosial, yang mungkin memperkuat ketahanan psikologis dalam konteks olahraga.